reduza os termos semelhantes efetuando as operações Indicadas :
a) 7x²-(6x²+9-2) + (-9x+4x²-3) =
b) (8ab-7bc+3ac) + (-5bc + 3ab - ac) =
Respostas
respondido por:
0
Resposta:
a) 7x²- (6x² + 9 - 2) + (-9x + 4x² - 3) =
7x²- (6x² + 7) - 9x + 4x² - 3 =
7x²- 6x² - 7 - 9x + 4x² - 3 =
7x²- 6x² + 4x² - 9x - 3 - 7 =
5x² - 9x - 10
b) (8ab - 7bc + 3ac) + (-5bc + 3ab - ac) =
8ab - 7bc + 3ac - 5bc + 3ab - ac =
8ab + 3ab - 7bc - 5bc + 3ac - ac =
11ab - 12bc + 2 ac
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás